THE PHENOMENON OF ETHNO-CULTURAL RESILIENCE IN THE CONTEXT OF TRAUMATIC WAR EXPERIENCES - Shostak, Uliana; Shui, Natalia (Personality and environmental issues, 2025)
The purpose of the work is the theoretical and methodological analysis of the ethno-cultural phenomenon of resilience in the context of traumatic war experience in Ukraine, with an emphasis on the relationship between individual psychological resources and collective cultural meanings that ensure the vitality of the individual and the community. The research methodology is based on systemic, cultural-historical, and phenomenological approaches to studying personality in crisis conditions, the principles of humanistic psychology, and the concepts of psychological resilience (M. Rutter, B. Cyrulnik, A. Masten, M. Ungar) and ethnopsychology. We used methods of theoretical generalisation, content analysis of scientific sources, phenomenological description of cultural displays of resilience, and structural-functional analysis of ethno-cultural mechanisms of adaptation. Scientific novelty lies in revealing ethno-cultural resilience as an integrative phenomenon that combines individual and collective resources of survival; in determining its functions (protective, identifying, integrative, restorative, creative, and communicative) in the context of war trauma; in distinguishing symbolic, linguistic, and creative mechanisms through which culture ensures the psychological resilience of Ukrainiansу. Conclusion. The ethno-cultural resilience of Ukrainians in wartime shows up in their ability to preserve and reproduce cultural meanings even in traumatic situations, turning pain into a resource for spiritual growth. Through language, song, traditions, art, and shared symbols, Ukrainian culture performs therapeutic, restorative, and unifying functions, strengthening the internal resilience of society. Awareness and development of this phenomenon are important for post-war rehabilitation, educational policy, and the preservation of national identity.